An Overview of Sleep Quality in Early Adolescence with Smartphone Addiction in Kluwut Village, Wonosari District, Malang Regency: Gambaran Kualitas Tidur Pada Usia Remaja Awal Dengan Kecanduan Smartphone Di Desa Kluwut Kecamatan Wonosari Kabupaten Malang - Dewi, Niken Ismia; Prastiwi, Swito (Jurnal Keperawatan Terapan, 2023)
Technology, information, and communication are developing very rapidly. One of the evidence that is often encountered everyday is the smartphone. Smartphones are very helpful to human activities, but also have negative effects if the user is not wise when using them. The purpose of this study is to determine the sleep quality of early age adolescents (12–15 years old) who experience smartphone addiction in Kluwut Village, Wonosari District, Malang Regency. This research uses descriptive method of case study. The study subjects were 2 teenagers, namely An. K as the first subject and An. N as the second subject. The data was taken by interview and filling out the Smartphone Addiction Scale (SAS) questionnaire to determine the level of addiction to smartphones and the Pittsburgh Sleep Quality Index (PSQI) to determine the quality of sleep. The results of this study showed that the first subjects (An. K) who experienced a high addiction to smartphones and the second subject (An. N) those who experience moderate addiction to smartphones tend to have low sleep quality with a total score >5. The conclusion of this study is that excessive smartphone use is proven to affect sleep quality in terms of lifestyle factors and habits. The next researcher is expected to examine more deeply about other factors that affect sleep quality, including fatigue, nutrition and food, and the environment.